Pentadbiran Zakat dan Kesedaran Masyarakat Islam Membayar Zakat di Daerah Kota Belud Sabah (Sains Humanika, 2014)
Collection of Zakat and the distribution of its proceeds in Malaysia, and in this case in the state of Sabah are under the jurisdiction of the Religious Council as provided by the Constitution and state enactment. The never ending question pertaining to this responsibility is on the performance of religious authorities in managing the affair of zakat. Looking at one angle of the society awareness on the obligation to pay zakat, this article attempts to investigate factors that inhibit the effiency of zakat administration of the state authorities. For this purpose the authors select the district of Kota Belut in the state of Sabah as model for this study. The methodology used in data collection is library research and field work (interviews and questionnaire). Analysis of the data is descriptive. Major findings of the article are that performance of zakat collection is much related to the understanding of the Muslims on the conditions and types of zakat and consequent of this, the pro-active role that should be taken by the authorities to dissiminate knowledge and understanding of zakat obligation.
Keywords: Zakat administration Sabah; zakat collection Sabah; zakat and society Sabah